1999
DOI: 10.1274/jmor.16.59
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Apoptosis and Extracellular Matrices in Granulosa Cells of Atretic Follicles in Porcine Ovaries.

Abstract: Abstract:The process of apoptosis of follicular granulosa cells in porcine ovaries during follicular atresia was investigated by in situ DNA 3'end-labeling at the level of individual cells. Histochemical changes in the follicular basement membrane (BM) were visualized by immunofluorescent staining of BM extracellular matrix (ECM) components, i.e. type IV collagen, laminin and fibronectin. At the first stage, granulosa cells located on the inner surface of the granulosa layer appeared to undergo apoptosis, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Strong expression of VE-cadherin was observed in a single cell layer directly attached to the basement membrane. As previously reported, ECM components of the follicular basement membrane may act as survival factors for follicular granulosa cells and theca interna cells directly a t ta ch ed to t he ba se men t m e mb ra ne [ 25 ] . Therefore, it is presumed that contact between the basement membrane and granulosa cells or theca interna cells has an essential role in maintaining growth and development of healthy follicles, and loss of contact induces apoptotic degeneration in follicular cells.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Strong expression of VE-cadherin was observed in a single cell layer directly attached to the basement membrane. As previously reported, ECM components of the follicular basement membrane may act as survival factors for follicular granulosa cells and theca interna cells directly a t ta ch ed to t he ba se men t m e mb ra ne [ 25 ] . Therefore, it is presumed that contact between the basement membrane and granulosa cells or theca interna cells has an essential role in maintaining growth and development of healthy follicles, and loss of contact induces apoptotic degeneration in follicular cells.…”
Section: Discussionmentioning
confidence: 63%
“…Many studies of follicular atresia have revealed the morphological and biochemical characteristics of the atretic follicles, which include detachment and degeneration of the granulosa cell layer [2][3][4], fragmentation of the basal membrane of the follicles [25], reduced DNA synthesis [26] and decreased estrogen production [27]. Recent studies h a v e s u g g es te d t h a t a po pt o s i s i s t h e k e y mechanism underlying ovarian follicular atresia [28], and have confirmed that granulosa cells first undergo apoptosis and that no apoptotic cell death occurs in cumulus cells in porcine atretic follicles [6].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of studies of follicular atresia have been reported, and they have revealed the morphological and biochemical characteristics of the atretic follicles, which include detachment and degeneration of the granulosa cell layer [2,3], fragmentation of the basal membrane of the follicles [15], reduced DNA synthesis [16] and decreased estrogen production [17]. Recent findings have suggested that apoptosis is the key mechanism underlying ovarian follicular atresia [18], and have confirmed that granulosa cells first undergo apoptosis and that no apoptotic cell death occurs in cumulus cells in porcine atretic follicles [11].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, larger numbers of proliferating cells were mainly seen in the outer region of the granulosa layer in healthy porcine follicles, and the granulosa cells located in the outer surface were in direct contact with the basement membrane. One likely candidate as a survival factor(s) is an extracellular matrix (ECM) component(s) in the basement membrane of follicles [15]. A previous in vitro study reported by Aharoni et al [29] revealed that ECM components of the basement membrane protected granulosa cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen sections of follicular sections of pig ovaries were prepared as described previously [38][39][40][41][42]. Briefly, individual preovulatory antral follicles, 3-5 mm in diameter, were dissected from ovaries obtained from mature sows at a slaughterhouse.…”
Section: Immunohistochemistry For Trail and Its Receptorsmentioning
confidence: 99%